Temperature-Sensitive Mutants Isolated from L Cells Persistently Infected with Newcastle Disease Virus - Preble, Olivia T. (1972)
Virus mutants (NDV(pi)) isolated from L cells persistently infected with the Herts strain of Newcastle disease virus have been previously reported by this laboratory to differ from the wild-type virus (NDV(o)) in several physical and biological properties. It has now been determined that, in addition to these differences, the NDV(pi) mutants are also spontaneously selected temperature-sensitive mutants. The temperature sensitivity of 10 NDV(pi) clones was confirmed by temperature inhibition, plaquing efficiency, and single-cycle yield experiments. The cut-off temperature, at which more than 90% of virus replication is inhibited was between 41 and 42 C. All 10 NDV(pi) clones were also found to be defective in virus-specific ribonucleic acid (RNA) synthesis in infected chick embryo cells at 42 C and are tentatively classified as RNA(−). The possible relationships of the temperature sensitivity, the other NDV(pi) properties, and the maintenance of the persistently infected state are discussed.